Opolnomočenje posameznikov na ravni soseske - Filipovič Hrast, Maša (Teorija in praksa, 2016)
Today we are facing the need to renovate large housing estates with multi-family buildings, as they are facing various problems. The key element of such renewal is the participation of residents, which is based on the feeling of control over the quality of life in a neighbourhood, i.e. the empowerment of neighbourhood residents. The article presents the results of a survey on neighbouring relations carried out in the Municipality of Ljubljana. Empowerment was operationalised with three dimensions: attitudes, knowledge and behavioural. We analyse the factors linked with the empowerment of residents in multi-family buildings. These are socio-demographic factors as well as attachment to the neighbourhood, contact with neighbours and trust among neighbours.
Keywords: Attachment behavior; attachment theory; Ljubljana (Slovenia; Mestna občina); Ljubljana (Slovenija; mestna občina); Navezanost; Neighbourhood; opolnomočenje; Participacija; Participation; Soseska